2016
DOI: 10.5010/jpb.2016.43.4.473
|View full text |Cite
|
Sign up to set email alerts
|

Four multiplex PCR Sets of 11 LM Maize for LMO environmental monitoring in Korea

Abstract: This is an Open-Access article distributed under the terms of the Creative Commons Attribution Non-Commercial License (http://creativecommons.org/licenses/by-nc/4.0) which permits unrestricted non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited.Abstract With the increasing development and commercial use of genetically modified maize, it is essential to develop an appropriate method for detection of individual LMO (Living modified organism) events for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…For high-sensitive detection, large amount of DNA as template is used; however, environmental sample of LMO cannot ensure DNA quality and quantity. Several testing methods released by developers or regulators and several previously reported GMO detection methods recommend that the minimum amount of purified DNA required is 40-100 ng in total reaction volume [6,10,11]. In this study, we detected LMOs using the newly developed multiplex PCR method, which required only 12.5 ng of purified DNA.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…For high-sensitive detection, large amount of DNA as template is used; however, environmental sample of LMO cannot ensure DNA quality and quantity. Several testing methods released by developers or regulators and several previously reported GMO detection methods recommend that the minimum amount of purified DNA required is 40-100 ng in total reaction volume [6,10,11]. In this study, we detected LMOs using the newly developed multiplex PCR method, which required only 12.5 ng of purified DNA.…”
Section: Discussionmentioning
confidence: 96%
“…The multiplex PCR results with randomly mixed RM mixtures suggested that this method can identify all LMO stacks, including the four LM cotton varieties that will be approved in the future. The multiplex PCR method was applied to identify LM samples, which were collected from environmental monitoring [9][10][11]. To verify the application of multiplex PCR method in LMO monitoring, we used LM cotton samples collected from an LMO monitoring project in the Republic of Korea in 2018.…”
Section: Verification Of the Efficiency Of Multiplex Pcrmentioning
confidence: 99%
“…Based on the simplex PCR results, we optimized a novel multiplex PCR analysis for four LM soybeans (CV127, MON87705, FG72 and MONM87701). Previous studies revealed that optimization of multiplex PCR was very delicate and difficult because of insertion gene similarity, difference of primer and PCR condition [8][9][10]. In this study, we tried to fix primer concentration and PCR reaction condition to optimize all PCR reaction products.…”
Section: Establishment Of Simultaneous Multiplex Pcrmentioning
confidence: 99%
“…[7,8]. Moreover, the detection methods were further elaborated for the multiplex PCR which was applicable to the analysis of LMO monitoring samples [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Since 2009, the MOE and National Institute of Ecology (NIE) have been conducting The Environmental LMO Monitoring and Post-Management Project [9,10]. In the project, the natural environmental leakage of LM crops such as cotton, maize, soy bean, and canola was monitored and the risk assessment and management of released LMOs was performed [11][12][13]. A specific LMO detection method is crucial to determine whether the samples collected in this project contain LMOs [14,15].…”
Section: Introductionmentioning
confidence: 99%